The current world economic situation and its impact on China's foreign exchange and foreign investment - Huang, Bei (Transactions on Economics, Business and Management Research, 2024)
In 2023, the world economy shows clear growth divergence and complex changes driven by technology. The United States economy is showing strong resilience, but its growth is still affected by inventory movements. In contrast, the economies of the euro area and Japan face serious challenges, while some emerging economies, such as India and Vietnam, show signs of a positive recovery. Meanwhile, prices in major economies generally rose, international trade improved slightly and financial markets picked up. In the coming period of time, the world economy is likely to be in the process of bottoming out and bottoming out, will continue to affect China's foreign trade and foreign investment fundamentals, China should overcome the risks and challenges, enhance confidence, increase policy support, and make every effort to create an environment conducive to the development of an export-oriented economy, and actively tap the new advantages of industrial competition, and to promote China's sustainable development of the economy.